Efficacy and safety of PD-1/PD-L1 inhibitors alone or in combination in the treatment of metastatic or advanced renal cell carcinoma: a network meta-analysis - Dongli Zhang; Chong Shen; Weichuan Zhang; Haibin Chen; Jianjun Zhao (Frontiers in Immunology)
BackgroundThis study systematically reviews the efficacy and safety of the single or combined use of programmed factor 1 (PD-1)/programmed factor 1 ligand (PD-L1) inhibitors for treating metastatic or advanced renal cell carcinoma (RCC).MethodsRelevant articles were collected for meta-analysis through searches on PubMed, Web of Science, Embase, Cochrane Library, and Clinical Trials, as well as for relevant randomized controlled experiments.ResultsBased on eleven studies, the effectiveness of the experimental group was found to be significantly better than the control in terms of overall survival (OS) [R=0.74, 95%CI: 0.69~0.80, P<0.00001], progression-free survival (PFS) [HR=0.68, 95%CI: 0.57~0.81, P<0.0001], objective response rate (ORR) [RR=1.71, 95%CI: 1.39~2.12, P<0.00001], complete response rate (CR) [RR=2.99 95%CI: 2.34~3.83, P<0.0001], partial response rate (PR) [RR=1.56, 95%CI: 1.20~2.01, P=0.001], and disease control rate (DCR) [RR=1.13, 95%CI: 1.06~1.20, P<0.0001]. No statistical significance was observed between the experimental and control groups in overall adverse reactions (AEs) [RR=1.01, 95%CI: 0.98~1.04, P=0.598], the incidence of stage I~II adverse reactions [RR=1.02, 95%CI: 0.88~1.17, P=0.818], or stage III~V adverse reactions [RR=0.98, 95%CI: 0.81~1.18, P=0.817]. Regarding subgroup analysis, the incidence of dysphonia, rash, hypothyroidism, arthralgia, and pruritus in the experimental group was significantly higher than in the control. Compared with the control group, the incidence of diarrhea, nausea, indigestion, and fatigue in the experimental group was not statistically significant.ConclusionA good efficacy was found in treating metastatic or advanced RCC using PD-1/PD-L1 inhibitors alone or in combination, which significantly improved and enhanced OS, PFS, ORR, CR, PR, and DCR in patients with RCC. The incidence of adverse reactions in patients was not increased, and adverse reactions were controllable. These findings indicate that the single or combined use of PD-1/PD-L1 inhibitors shows good efficacy and safety in the treatment of metastatic or advanced RCC.